MANAJEMEN KOMUNIKASI PEMASARAN RUMAH MAKAN 17 PROPINSI CABANG ABDULLAH DAENG SIRUA MAKASSAR - Fitra; Mahmud; T.G. Tanrasula, Muh. Agung (LPPM Universitas Muhammadiyah Bulukumba, 2025)
This study analyzes the marketing communication strategies of RumahMakan 17 Propinsi, Abdullah Daeng Sirua branch, Makassar, using the MarketingMix (7P) concept and identifies the barriers encountered in its implementation. Aqualitative approach with descriptive analysis was employed, with data collectedthrough interviews, observations, and documentation from five informants, includingthe owner, employees, and customers. The findings reveal that the marketingcommunication strategies encompass high-quality products, affordable pricing,strategic location, promotion through personal selling and word of mouth, friendlyservice, efficient processes, and authentic physical evidence. However, theimplementation faces challenges such as message delivery errors, environmentalnoise, misunderstandings of local menu terms, and customers’ psycho-social factors.The study recommends adopting digital technologies like social media and employeetraining to enhance marketing communication effectiveness. These findings provideinsights into the relevance of traditional strategies in the digital era and the need for ahybrid approach to improve competitiveness.